RATIONING AND ASSESSMENT OF OPERATIONAL TECHNICAL CHARACTERISTICS OF AIRCRAFT - Тамаргазін, О.; Ліннік, І.; Лінник, О. (Science-based technologies, 2012)
Questions o f formation operational and technical characteristics of modern flight vehicles are considered. The offered approach can be used for lethal vehicles of different classes and appointment. It is complex and adapted for operation conditions of particular type of the lethal vehicle on stages of life cycle and allows to reduce time of formation of effective operation-technical characteristics of lethal vehicles at development stages of their operation and their updating throughout all term of type operation of a flight vehicle before discarding.